Can Advertising Investments Counter the Negative Impact of Shareholder Complaints on Firm Value?. (July 2019) - Wies, Simone; Hoffmann, Arvid Oskar Ivar; Aspara, Jaakko; Pennings, Joost M.E.
Shareholder complaints put pressure on publicly listed firms, yet firms rarely directly address the actual issues raised in these complaints. The authors examine whether firms respond in an alternative way by altering advertising investments in an effort to ward off the financial damage associated with shareholder complaints. By analyzing a unique data set of shareholder complaints submitted to S&P 1500 firms between 2001 and 2016, supplemented with qualitative interviews of executives of publicly listed firms, the authors document that firms increase advertising investments following shareholder complaints and that such an advertising investment response mitigates a postcomplaint decline in firm value. Furthermore, results suggest that firms are more likely to increase advertising investments when shareholder complaints are submitted by institutional investors, pertain to nonfinancial concerns, and relate to topics that receive high media attention. The findings provide new insights on how firms address stock market adversities with advertising investments and inform managers about the effectiveness of such a response.